Usulan Perencanaan Produksi dengan Pendekatan Material Requirement Planning (MRP) - Afif Syarifuddin Muflih; Reni Amaranti; Agus Nana Supena (Jurnal Riset Teknik Industri, 2024)
Abstract. PT Nazar Aneka Warna is a manufacturing company that focuses on the production of wall paint with pail (bucket) and kilo units, this company implements a make-to-stock marketing strategy. Based on the research that has been conducted, there are problems that currently occur, namely the number of overproduction products that cause accumulation, and the company does not have a raw material procurement plan for future production needs. As a result of the problem of overproduction, it can cause the product to expire if stored for a long period of time, the expired product needs to be reprocessed so that it can be marketed again, which will increase the expenditure of greater costs. Indications of the problems encountered are due to the low level of accuracy of demand forecasting and excessive production levels in meeting market demand so that the number of return products is found due to unsold products, and does not have strategic planning for raw material procurement schedules for production needs. The proposed research is a production plan with Material Requirement Planning (MRP) approach. The results that have been obtained include demand forecast data for the next period with the selected method, namely Double Exponential Smoothing Holt and has been validated with a Moving Range Chart (MRC) graph, aggregate production plan data with a total production cost of Rp 264.752.418, master production schedule data for each product, and raw material procurement schedule data with lot sizing at level 1 and level 2 using the selected method, namely Period Order Quantity (POQ) which results in inventory costs that need to be incurred of Rp 166.751.807.508. Abstrak. PT Nazar Aneka Warna merupakan perusahaan manufaktur yang berfokus pada produksi cat tembok dengan satuan pail (ember) dan kiloan, perusahaan ini menerapkan strategi pemasaran secara make to stock. Berdasarkan penelitian yang telah dilakukan, ditemui permasalahan yaitu terdapat sejumlah produk stok yang berlebih (overproduction) sehingga menyebabkan penumpukan, serta perusahaan tidak memiliki rencana pengadaan bahan baku untuk keperluan produksi pada masa yang akan datang. Akibat permasalahan dari overproduction dapat menyebabkan produk menjadi kedaluwarsa jika tersimpan dalam jangka waktu yang panjang, apabila produk kedaluwarsa diperlukan reprocessing agar dapat dipasarkan kembali yang mana akan menambah pengeluaran biaya (cost) lebih besar. Indikasi permasalahan yang ditemui yaitu karena tingkat akurasi peramalan permintaan rendah dan tingkat produksi berlebihan dalam memenuhi permintaan pasar sehingga ditemui jumlah produk return akibat produk tidak laku terjual, serta tidak memiliki perencanaan yang strategis terhadap jadwal pengadaan bahan baku untuk kebutuhan produksi. Usulan penelitian yang dilakukan yaitu rencana produksi dengan pendekatan Material Requirement Planning (MRP). Hasil yang telah didapat diantaranya data ramalan permintaan untuk periode selanjutnya dengan metode yang terpilih yaitu Double Exponential Smoothing Holt serta telah di validasi dengan grafik Moving Range Chart (MRC), data rencana produksi agregat dengan jumlah biaya produksi sebesar Rp 264.752.418, data jadwal induk produksi untuk masing – masing produk, serta data jadwal pengadaan bahan baku dengan lot sizing pada level 1 dan level 2 menggunakan metode terpilih yaitu Period Order Quantity (POQ) yang menghasilkan biaya persediaan yang perlu dikeluarkan sebesar Rp 166.751.807.508.